New media, new profiles and emotional connectivity with the audience: journalists in professional praxis - Sánchez Gonzales, Hada M.; Méndez Muros, Sandra (CIC. Cuadernos de Información y Comunicación, 2013)
This paper aims to shed light on a Journalism that does not remain exempt from the innovations that Web 2.0 brings inside. The media try to adapt to the needs of two hot topics: digital convergence and social means, and the journalists have to confront the new professional challenges as consequence of the technological, media and social revolution. It is determined the existence of the new professional profiles upon labor demand and in the professional exercise, the use of the social platforms by the journalists and the emotional connectivity that is established by the readership in these environments. We employ the poll as quantitative and qualitative methodological technology to analyze at local level the opinion of the journalists of two newspapers edited in Seville: Abc and Diario de Sevilla.
Keywords: New professional profiles; digital Journalism; social means; press of Seville